Uporaba metod operacijskih raziskav pri načrtovanju kmetijske proizvodnje - Žgajnar, Jaka (Uporabna informatika (Ljubljana), 2011)
In this paper agriculture as a sector with extremely complex management problems is presented. Most frequently applied mathematical programming methods for resource allocation considering risk are being presented. The paper illustrates innovative approach of linking different methods enabling support for short-term operative-tactical planning. The proposed approach enables the analysis of hypothetical or real agricultural holding. It takes into account agro-technical, environmental and economic circumstances. The application of the developed model enables one to evaluate farmers developmentperspectives from different points of view, indicating possibilities for increasing added value in farming. The model application hasbeen illustrated in the case of a dairy farm.
Keywords: agriculture; kmetijstvo; modeli za podporo odločanju; optimiranje; matematično programiranje; kmetijsko obratoslovje